Peculiarities of pyrrhotite mineralization in the Chertovo Koryto deposit (Patom Uplands); IOP Conference Series: Earth and Environmental Science; Vol. 43 : Problems of Geology and Subsurface Development - Sinkina E. A. Ekaterina Andreevna; Savinova O. V. Olesya Vyacheslavovna; Nepryakhina O. B.; Kolbysheva Yu. V. Yuliya Vladimirovna (Ore Deposits: Current Prospecting and Exploration Methods, 2016)
Title screen